Multibody System Dynamics, Robotics and Control - Gattringer, Hubert; Gerstmayr, Johannes; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2013)
The volume contains 19 contributions by international experts in the field of multibody system dynamics, robotics and control. The book aims to bridge the gap between the modeling of mechanical systems by means of multibody dynamics formulations and robotics. In the classical approach, a multibody dynamics model contains a very high level of detail, however, the application of such models to robotics or control is usually limited. The papers aim to connect the different scientific communities in multibody dynamics, robotics and control. Main topics are flexible multibody systems, humanoid robots, elastic robots, nonlinear control, optimal path planning, and identification.
Time-optimal path planning along specified trajectories -- Efficient online computation of smooth trajectories along geometric paths for robotic manipulators -- Constraint and dynamic analysis of compliant mechanisms with a flexible multibody modelling approach. - Sensor data fusion for the localization and position control of one kind of omnidirectional mobile robots. - Modelling and control of infinite-dimensional mechanical systems: a port-Hamiltonian approach. - Passivity-based tracking control of a flexible link robot. - Norm-optimal iterative learning control for a pneumatic parallel robot. - Balance and posture control for biped robots. - Robot-based testing of total joint replacements. - Dynamics and control of the biped robot Lola. - Automated kinematics reasoning for wheeled mobile robots. - Automatic paramenter identification for mechatronic systems. - Crane operators training based on the real-time multibody simulation. - On a momentum based version of Lagrange's equations. - Vibration control and structural damping of a rotating beam by using piezoelectric actuators. - Multibody dynamics approaches to biomechanical applications to human motion tasks. - Application examples of wire robots.
Keywords: Engineering; Vibration; Engineering; Vibration, Dynamical Systems, Control; Control, Robotics, Mechatronics